Natural Exon Skipping Sets the Stage for Exon Skipping as Therapy for Dystrophic Epidermolysis Bullosa - Jeroen Bremer; Elisabeth H. van der Heijden; Daryll S. Eichhorn; Rowdy Meijer; Henny H. Lemmink; Hans Scheffer; Richard J. Sinke; Marcel F. Jonkman; Anna M.G. Pasmooij; Peter C. Van den Akker (Elsevier, 2019)
Dystrophic epidermolysis bullosa (DEB) is a devastating blistering disease affecting skin and mucous membranes. It is caused by pathogenic variants in the COL7A1 gene encoding type VII collagen, and can be inherited dominantly or recessively. Recently, promising proof-of-principle has been shown for antisense oligonucleotide (AON)-mediated exon skipping as a therapeutic approach for DEB. However, the precise phenotypic effect to be anticipated from exon skipping, and which patient groups could benefit, is not yet clear. To answer these questions, we studied new clinical and molecular data on seven patients from the Dutch EB registry and reviewed the literature on COL7A1 exon skipping variants. We found that phenotypes associated with dominant exon skipping cannot be distinguished from phenotypes caused by other dominant DEB variants. Recessive exon skipping phenotypes are generally relatively mild in the spectrum of recessive DEB. Therefore, for dominant DEB, AON-mediated exon skipping is unlikely to ameliorate the phenotype. In contrast, the overall severity of phenotypes associated with recessive natural exon skipping pivots toward the milder end of the spectrum. Consequently, we anticipate AON-mediated exon skipping for recessive DEB caused by bi-allelic null variants should lead to a clinically relevant improvement of this devastating phenotype. Keywords: exon skipping, therapy, dystrophic epidermolysis bullosa, splicing, genotype-phenotype correlation